Therapeutic Efficacy of Esomeprazole in Cotton Smoke-Induced Lung Injury Model - Nelson, Christina; Lee, Jameisha; Ko, Kang; Sikora, Andrew G.; Bonnen, Mark D.; Enkhbaatar, Perenlei; Ghebre, Yohannes T. (Frontiers in Pharmacology, 2017)
Proton pump inhibitors (PPIs) are well-known antacid drugs developed to treat gastric disorders. Emerging studies demonstrate that PPIs possess biological activities that extend beyond inhibition of H+/K+ ATPase (proton pumps) expressed in parietal cells of the stomach. Some of the extra-gastric activities of PPIs include modulation of epithelial, endothelial and immune cell functions. Recently, we reported that PPIs suppress the expression of several proinflammatory and profibrotic molecules, as well as enhance antioxidant mechanisms in order to favorably regulate lung inflammation and fibrosis in an animal model of bleomycin-induced lung injury. In addition, several retrospective clinical studies report that the use of PPIs is associated with beneficial outcomes in chronic lung diseases including idiopathic pulmonary fibrosis (IPF) and chronic obstructive pulmonary disease (COPD). Based on these preclinical and clinical observations, we hypothesized that PPIs ameliorate smoke-induced lung injury. Accordingly, we evaluated the pharmacological efficacy of the PPI esomeprazole in a mouse model of cotton smoke-induced lung injury. The animals were exposed to cotton smoke for 3-weeks in the presence or absence of esomeprazole treatment. We found that therapeutic administration of esomeprazole significantly inhibited the progression of fibrosis throughout the lungs of the animals in this group compared to controls. In addition, esomeprazole also reduced circulating markers of inflammation and fibrosis. Overall, our work extends the emerging anti-inflammatory and antifibrotic potential of PPIs and their role in modulation of chronic lung diseases.